INVESTIGATING THE EFFECTIVE FACTORS ON THE TENDENCY TO PRAY AND HOLDING CONGREGATIONAL PRAYERS IN STUDENTS OF KERMANSHAH UNIVERSITY OF MEDICAL SCIENCES - Mahvash Kahrizi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Introduction: Prayer and its performance is one of the major religious characteristics in the religion of Islam which has important functions such as deterrence of prostitution and denial, cultivation and health of the soul, reducing social abnormalities among others. On the other hand, considering the importance of youth in promoting the growth of the current society, this study was conducted to investigate the factors affecting the tendency of students to perform prayers and congregational prayers. Materials and methods: The present study is a descriptive-analytical and cross-sectional one conducted by the survey on all students studying in the second half of 1397 in all medical schools of Kermanshah. The instrument of the study was a two-part questionnaire, including demographic information form and researcher-made questionnaire of tendency to pray and congregational prayers. Data were collected statistically using SPSS-18 statistical software. Results: The results showed that the educational level, gender and religious beliefs of students with a tendency to prayer were significant, so that the tendency to pray in postgraduate students was more than the other two levels (p <0.001). The tendency to pray in students has generally been high. The results showed that the sensitivity of the family to immediate prayer, socializing with relatives bound to the prayer, praying by the family at home are known as motivating factors (p <0.001). The long speech of the Imam of the congregation between the two prayers and the opposition of friends to participate in the congregational prayer are known to prevent students from participating (p <0.001).